Comparison of Intra-Peritoneal Bupivacaine with Saline Solution after Laparoscopic Cholecystectomy - Muhammad Hassaan, Jehanzaib Rashid, Rana Shoaib Aslam, Assam Arshid, Syed Asghar Naqi, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the mean pain score of intra-peritoneal bupivacaine versus saline solution in patients undergoing laparoscopic cholecystectomy for cholelithiasis. Material and methods: Between April 2021 to October 2021, total 100 diagnosed patients of cholelithiasis having age 18-70 years, of either gender planned to undergo laparoscopic cholecystectomy under general anesthesia with ASA I-II were selected from Department of Surgery, Mayo Hospital, Lahore. In Bupivacaine group, Intra-peritoneal Bupivacaine was given. In Saline group, Intra-peritoneal Saline Solution was given. Laparoscopic Cholecystectomy was performed. Mean pain score was compared between Bupivacaine group and Saline group. Results: Patients having age 18-70 years were selected. Mean age was 43.80±15.60 years. The mean age of patients in Bupivacaine group was 43.3±16.0 years and in Saline group was 44.3±15.3 years. In Bupivacaine group and Saline group, mean pain score was 1.82±0.75 and 4.72±1.20 respectively. Significantly (P=0.000) low mean pain score was noted in Bupivacaine group as compared to Saline group. Conclusion: There is a significant difference in mean pain score of intra-peritoneal bupivacaine versus saline solution in patients undergoing laparoscopic cholecystectomy for cholelithiasis. Keywords: Cholelithiasis, Cholecystectomy, Intra-peritoneal Bupivacaine, Saline Solution.